A Prospective Randomized Crossover Study on the Comparison of Cotton Versus Waterproof Cast Liners. (March 2016) - Guillen, Philip T.; Fuller, Corey B.; Riedel, Barth B.; Wongworawat, Montri D.
Background: Many fractures are treated with casting which can cause complications likely from inability to wash the extremity. Gore-Tex-based waterproof cast liner has been compared with cotton liner and shown to be superior in physician and patient scoring but also has high cost and difficult application. The purpose of this study is to compare newer generation waterproof liners with traditional cotton liner. It is the first study to compare this new waterproof liner and cotton liner in a crossover model, allowing patients to swim in the pool with the cast.Methods: Twenty patients (ages 3-30) with upper extremity injuries were randomized to waterproof-liner or cotton-liner casts made of fiberglass. Patients would switch cast liners halfway between their treatments to fulfill crossover criteria. All fractures were within a 2-week period from original incident. At each clinic visit, patients evaluated comfort parameters through questionnaires, and physicians rated skin condition. Patients were also asked which cast liner they preferred at the end of the study.Results: There were no unscheduled cast changes. The waterproof-liner group had better scores for odor ( P = .041), sweat ( P = .016), and overall physician-rated score ( P = .038). There was no significant difference in other patient-rated parameters. Seventy-five percent of patients preferred waterproof casting to the cotton liner.Conclusions: This new waterproof cast liner, compared with cotton cast liner, had better odor, sweat, and overall physician scores. The waterproof liners allow patients to rinse casts daily, and the majority of patients prefer waterproof to cotton liner.